Electrical Conductivity Studies of Nanophase Copper Nickel Ferrite Prepared by Solid State Reaction Technique - Mahalakshmi1, S.; Srinivasa Manja2, K. (Asian Journal of Chemistry, 2013)
The electrical properties of nanocrystalline copper nickel ferrites having general chemical formula CuxNi(2-x)Fe2O4 with x varied from 0.2 to 0.9 have been studied. The AC electrical conductivity has been measured as a function of frequency in the range 50 kHz-900 kHz at room temperature 296 K. Prepared samples show the usual dielectric dispersion having Maxwell-Wagner-type interfacial polarization. Reduction in dielectric constant, loss tangent and AC conductivity has been observed with frequency. Dielectric loss tangent also increases with the increase of copper content in the sample which may be due to hopping of Fe2+ ions.